Бесы: [роман] / Федор Достоевский - Достоевский Федор Михайлович (Мировая классика, 2018)
Экземпляры: ф.4 (20190228) / Инвентарный номер: 56621 / Цена: 150.00 / Авт.знак: Д 70 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)1